TRANSLANGUAGING PRACTICES IN SONGS BY INDONESIAN SINGERS - Sagimin, Eka Margianti; Sapitri, Ariyanti (Lexeme : Journal of Linguistics and Applied Linguistics, 2023)
The practice of translanguaging in Indonesian songs by Indonesian singers is the primary focus of this paper. The objectives of the study are to categorize the types of translanguaging strategies used in songs, analyze how translanguaging is employed, and investigate why Indonesian artists use translanguaging in their songs. Using the qualitative method, this current study presents the translanguaging practice of the selected singer and its song. Weird Genius and Sara Fajira's song "Lathi," Atta Halilintar and Aurel Hermansyah's song "Hari Bahagia," Via Vallen's song "Holiday," Voice of Baceprot's song "School Revolution," and Bondan Prakoso and Fade 2 Black's song "Ya Sudahlah" are among the songs that are used as the sample of this study. The theory of Lucy Tse (1996) is used to identify the type of translanguaging and how to apply trans-languaging itself. Meanwhile, Charlotte Hoffman (1991) is used to examine the reason for using translanguaging. The results of the study showed that the 20 data used the same type of translanguaging, namely code-switching. In addition, this study also found the 20 data applied translanguaging in the same way, namely, using more than one language in one song and switching them from one lyric to another. The writer also found that showing group identity revealed the reason why Indonesian singers used translanguaging in their songs.